TiAl alloy, additive manufacturing composite process preparation method and application thereof
Patent Information
- Application Number
- CN202511848810.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-09
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2045-12-09
AI Technical Summary
[0003]然而,TiAl合金在实际应用过程中仍面临诸多制备挑战
本发明采用不同相对体积分数的Ti支架与Al粉复合构建预成形体,并通过激光粉末床熔融、热等静压工艺和热处理工艺制备TiAl合金。本发明通过合金的成分与增材制造复合工艺的灵活调控,使制备得到的TiAl合金具有优异的强度和韧性,其屈服强度≥672MPa,最大强度为≥750MPa,最大应变为≥9.0%。
Smart Images

Figure CN121696411B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of titanium-aluminum alloy manufacturing technology, specifically to a TiAl alloy and its additive manufacturing composite process preparation method and application. Background Technology
[0002] With the rapid development of aerospace technology, low-pressure turbine blades face higher requirements in terms of weight and overall performance. TiAl alloys, as intermetallic compounds possessing low density, high specific strength, and excellent high-temperature oxidation resistance, have shown broad application prospects in hot-end components such as low-pressure turbine blades for aero-engines in recent years. Compared to traditional nickel-based superalloys, TiAl alloys have only about half the density, significantly reducing the overall engine weight and improving the thrust-to-weight ratio. Furthermore, TiAl alloys maintain good mechanical strength and oxidation stability within the service temperature range of 600–900°C, making them one of the ideal materials for achieving lightweight and high-efficiency engines.
[0003] However, TiAl alloys still face numerous manufacturing challenges in practical applications. On the one hand, due to their poor room-temperature plasticity, traditional casting and forging processes struggle to produce blades with complex structures. On the other hand, while additive manufacturing technology can directly form complex shapes and offers significant geometric flexibility, its high temperature gradient, localized heating, and cyclic heating characteristics easily lead to compositional fluctuations, non-uniform microstructure, and defects such as cracks, voids, and segregation during TiAl alloy forming. Ultimately, this results in poor strength and toughness, severely restricting its engineering applications. Furthermore, existing additive manufacturing technologies often use alloy powders for alloy preparation. These powders are costly, prone to cracking due to residual stress during the preparation process, and their fixed composition prevents flexible control of the alloy phases and composition. Summary of the Invention
[0004] To address the problems existing in the prior art, the primary objective of this invention is to provide a method for preparing TiAl alloys.
[0005] Another object of the present invention is to provide a TiAl alloy.
[0006] Another object of the present invention is to provide the application of the above-mentioned TiAl alloy in the preparation of turbine blades.
[0007] Another object of the present invention is to provide a TiAl alloy turbine blade.
[0008] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a TiAl alloy includes the following steps: S1. Ti scaffolds were fabricated using a laser powder bed melting process; S2. Fill the Ti support with aluminum powder, seal it, and then perform hot isostatic pressing. S3. Perform heat treatment again to obtain the TiAl alloy; The energy density of the laser powder bed melting process is 60~70 J / mm². 3 ; The relative volume fraction of the Ti scaffold is 40-70%; The heat treatment includes a first heat treatment, the temperature of which is ≥800℃.
[0009] This invention employs laser powder bed melting to prepare Ti scaffolds with varying relative volume fractions. Aluminum powder is then filled into the Ti scaffolds, followed by a combination of hot isostatic pressing (HIP) and heat treatment to produce a unique TiAl alloy. During HIP and heat treatment, the Ti and Al phases interpenetrate, forming the TiAl alloy. Ultimately, a layered alloy phase distribution is formed at the interface between the titanium and aluminum phases, comprising Ti3Al (α2) and TiAl (γ) phases. This unique TiAl alloy exhibits excellent strength and toughness. The preparation method of this invention allows for flexible control of the alloy composition and the shaping of complex geometric morphologies, avoiding problems such as compositional fluctuations, inhomogeneous microstructure, and crack formation associated with traditional TiAl alloy powders in additive manufacturing.
[0010] This invention controls the generation of TiAl alloys with different crystalline phases by controlling the relative volume fraction of Ti support, the amount of aluminum powder added, and the corresponding process parameters, thereby achieving controllable adjustment of the composition and directional optimization of the performance of TiAl alloys.
[0011] The preparation method of this invention can promote the interdiffusion of Ti and Al elements, forming controllable Ti3Al (α2) phase and / or TiAl (γ) phase in different composition ranges. The heat treatment process can further promote the evolution of the alloy crystal phase.
[0012] Preferably, the diameter of the Ti support rod is 0.5~1.5mm.
[0013] Preferably, the parameters of the laser powder bed melting process are: laser power of 160~180W, scanning speed of 800~1000mm / s, laser vector spacing of 80~120μm, and layer thickness of 20~40μm.
[0014] More preferably, the parameters of the laser powder bed melting process are: laser power of 165~175W, scanning speed of 800~1000mm / s, laser vector spacing of 80~120μm, and layer thickness of 20~40μm.
[0015] Preferably, the energy density of the laser powder bed melting process is 60~65 J / mm². 3 .
[0016] Preferably, the hot isostatic pressing process includes: holding at 1200~1800℃ for 3~8h at a pressure of 1~3MPa; and then holding at 600~1000℃ for 4~6h at a pressure of 80~120MPa.
[0017] More preferably, the hot isostatic pressing process includes: holding at 1200~1600℃ for 3~5h at a pressure of 1~2MPa; and then holding at 600~800℃ for 4~5h at a pressure of 90~110MPa.
[0018] Preferably, the relative volume fraction of the Ti support can be any value in the range of 44~52%, 40~60%, and 53~70%.
[0019] In this invention, the relative volume fraction of the Ti scaffold corresponds to the Ti metal element content in the TiAl alloy. This invention sets the relative volume fraction of the Ti scaffold to 44-52%, which enables the controlled synthesis of a TiAl alloy dominated by the TiAl(γ) phase, with an alloy composition of Al: 48-56 at.% and Ti: 44-52 at.%. This invention also sets the relative volume fraction of the Ti scaffold to 53-70%, which enables the controlled synthesis of a TiAl alloy dominated by the Ti3Al(α2) phase + TiAl(γ), with an alloy composition of Al: 35-47 at.% and Ti: 53-70 at.%.
[0020] In this invention, the relative volume fraction of the Ti support is the ratio of the volume of the Ti support to the volume occupied by its completely dense, non-porous solid material under the same external contour dimensions.
[0021] Preferably, the aluminum powder has a particle size of 15~53μm.
[0022] It should be noted that, in specific embodiments, the raw materials used in this invention are pure Ti powder and pure Al powder, without any other doped metals.
[0023] Preferably, the seal is achieved using a directional energy deposition process.
[0024] More preferably, the parameters of the directional energy deposition process are: laser power 800~1600W, walking speed 0.36~0.6m / min, and wire feeding speed 0.6~2m / min.
[0025] Preferably, the first heat treatment temperature is 800~1400℃.
[0026] Preferably, the first heat treatment time is 48~140h.
[0027] More preferably, the first heat treatment time is 72~120h.
[0028] Preferably, the heat treatment further includes a second heat treatment.
[0029] More preferably, the second heat treatment temperature is 400~800℃.
[0030] More preferably, the second heat treatment temperature is 500~700℃.
[0031] More preferably, the second heat treatment time is 60-90 hours.
[0032] More preferably, the second heat treatment time is 60-80 hours.
[0033] Preferably, the Ti support has a lattice structure. Its crystal structure can be any crystal structure known in the art.
[0034] More preferably, the crystal structure is at least one of body-centered cubic, face-centered cubic, and hexagonal close-packed structures.
[0035] This invention also protects the TiAl alloy prepared by the above preparation method.
[0036] Preferably, the phase composition of the TiAl alloy, by volume percentage, is: TiAl: 2~8%, Ti3Al: 50~70%, TiAl3: 0.1~1%, with the remainder being Ti phase and / or Al phase.
[0037] More preferably, the phase composition of the TiAl alloy, by volume percentage, is: TiAl: 5.7%, Ti3Al: 61.8%, TiAl3: 0.6%, with the remainder being Ti phase and / or Al phase.
[0038] This invention also protects the use of the above-mentioned TiAl alloy in the preparation of turbine blades.
[0039] A TiAl alloy turbine blade includes a blade outer shell, a blade inner layer, and a blade root; the blade root is the aforementioned TiAl alloy.
[0040] Preferably, in the TiAl alloy turbine blade, the outer shell of the blade is a single γ-phase TiAl alloy, and the inner layer of the blade is composed of Ti support, with the relative volume fraction of the Ti support in the inner layer of the blade being 40~60%.
[0041] Preferably, the leaf root is a TiAl alloy with an α2+γ phase.
[0042] More preferably, the alloy composition of the blade shell is Al: 48~56 at.% and Ti: 44~52 at.%.
[0043] More preferably, the alloy composition of the leaf root is: Al: 35~47 at.%, Ti: 53~70 at.%.
[0044] Preferably, the TiAl alloy turbine blade is prepared by the above-described preparation method.
[0045] More preferably, the crystal structure of the Ti scaffold in the inner layer of the leaf is the same as the crystal structure of the Ti scaffold in the leaf root preparation process.
[0046] This invention provides a TiAl alloy turbine blade, which can be prepared by the above-mentioned additive manufacturing composite process or by the above-mentioned TiAl alloy. Its outer shell meets the anti-oxidation performance requirements of the blade, while the inner layer of the blade is a Ti support, meeting the requirement for lightweight blade design. The blade root, prepared using the method of this invention, is made of TiAl alloy, which, due to its excellent strength and toughness, meets the high toughness requirement of the blade root.
[0047] This invention relates to TiAl alloy turbine blades, which utilize the differences in phase composition to design and prepare alloys with different phase compositions in different parts, in order to meet the performance requirements of different parts.
[0048] Compared with the prior art, the present invention has the following beneficial effects: This invention employs Ti scaffolds with different relative volume fractions to construct preforms with Al powder, and then prepares TiAl alloys through laser powder bed melting, hot isostatic pressing, and heat treatment. By flexibly controlling the alloy composition and additive manufacturing process, this invention enables the prepared TiAl alloys to possess excellent strength and toughness, with a yield strength ≥672 MPa, a maximum strength ≥750 MPa, and a maximum strain ≥9.0%.
[0049] The preparation method of this invention allows for the free design of TiAl alloy products with complex geometries and the realization of high-quality forming of TiAl alloys. It enables controllable adjustment of the composition of TiAl alloys and directional optimization of their properties, effectively solving the formability problems such as cracking encountered in traditional methods of preparing TiAl alloys using alloy powder and additive manufacturing processes.
[0050] The TiAl alloy turbine blade provided by this invention has different TiAl alloy phase structures in different parts, which can realize the performance configuration on demand and controllable configuration, meet the local performance regulation and functional gradient, and thus obtain turbine blades with high temperature resistance on the surface and high strength and toughness in the core, thereby improving the service performance and service life of the turbine blade. Attached Figure Description
[0051] Figure 1 This is a partial phase equilibrium diagram of the TiAl alloy and a schematic diagram of the turbine blade of the present invention, wherein 1 is the outer shell of the blade; 2 is the inner layer of the blade; and 3 is the blade root.
[0052] Figure 2 This is a flowchart illustrating the preparation process of TiAl alloy in this embodiment of the invention, where a is the laser powder bed melting process for preparing Ti scaffolds; b is the injection of aluminum powder into Ti scaffolds; c is a schematic diagram of hot isostatic pressing; d is a microstructure diagram; e is a mechanical property test diagram; and f is a schematic diagram of TiAl alloy blades with different phase compositions.
[0053] Figure 3 These are sample images of Examples 1-3 and Comparative Example 5 after hot isostatic pressing.
[0054] Figure 4 The images shown are electron microscope images and EDS linear scan spectra of Example 1.
[0055] Figure 5 The images shown are electron microscope images and EDS linear scan spectra of Comparative Example 2.
[0056] Figure 6 The diagram shows the phase composition statistics of Example 1, Comparative Example 2, and Example 1 before heat treatment.
[0057] Figure 7 Electron micrographs of Example 1(a), Comparative Example 2(b), and Example 1(c) before heat treatment. Detailed Implementation
[0058] The present invention is further illustrated below with reference to specific embodiments. These embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Experimental methods in the following embodiments that do not specify specific conditions are generally performed under conventional conditions in the art or as recommended by the manufacturer; the raw materials and reagents used, unless otherwise specified, are all commercially available from the conventional market. Any non-substantial changes and substitutions made by those skilled in the art based on the present invention are within the scope of protection claimed by the present invention.
[0059] In this invention, the relative volume fraction of the Ti support is the ratio of the volume of the Ti support to the volume occupied by its completely dense, non-porous solid material under the same external contour dimensions.
[0060] Example 1 This embodiment provides a TiAl alloy, the preparation method of which includes the following steps: S1. A Ti scaffold with a relative volume fraction of 50% and a body-centered cubic crystal structure was designed. The scaffold was made of thin rods with a diameter of 0.75 mm. The Ti scaffold was prepared by laser bed fusion (LBPF). The forming parameters of LBPF were: laser power of 170 W, scanning speed of 900 mm / s, laser vector spacing of 100 μm, layer thickness of 30 μm, and laser energy density of 63 J / mm². 3 .
[0061] S2. Treat the Ti substrate with an acid solution to remove the oxide film on the substrate surface; fill the Ti substrate with aluminum powder and seal it using a directional energy deposition (DED) process. The process parameters for DED are: laser power of 1200W, travel speed of 0.5m / min, and wire feed speed of 1.2m / min; then perform hot isostatic pressing (HIP), specifically: first, hold at 1200℃ for 3 hours while applying a pressure of 1MPa; cool for 25 minutes to reduce the temperature to 600℃, while increasing the pressure to 100MPa and holding for 4 hours; after holding, slowly cool to room temperature in the furnace to obtain the TiAl alloy preform.
[0062] S3. Then perform a first heat treatment at a temperature of 1000℃ for 120 hours to obtain the TiAl alloy. The phases of the TiAl alloy include Ti3Al(α2) phase and TiAl(γ) phase, and its alloy composition is: Al: 50 at.% and Ti: 50 at.%.
[0063] Example 2 This embodiment provides a TiAl alloy, the preparation method of which differs from that of Embodiment 1 in that: in S1, a Ti support with a relative volume fraction of 50% is designed, the support is a thick rod with a diameter of 1 mm; the rest is the same as in Embodiment 1.
[0064] Example 3 This embodiment provides a TiAl alloy, the preparation method of which differs from that of Embodiment 1 in that: in S1, a Ti support with a relative volume fraction of 70% is designed, the support is a thick rod with a diameter of 1 mm; the rest is the same as in Embodiment 1.
[0065] Example 4 This embodiment provides a TiAl alloy whose preparation method differs from that of Embodiment 2 in that: in S3, the heat treatment includes a first heat treatment and a second heat treatment. The first heat treatment temperature is 1000℃ and the heat treatment time is 120h, and the second heat treatment temperature is 600℃ and the heat treatment time is 72h.
[0066] Example 5 This embodiment provides a TiAl alloy turbine blade, including a blade outer shell, a blade inner layer, and a blade root; the specific structure is as follows: Figure 1 As shown. The outer shell of the blade is a single γ-phase TiAl alloy with Al: 48-56 at.% and Ti: 44-52 at.%; the inner layer of the blade is composed of a Ti support, the relative volume fraction of which can be any value between 40% and 60%, and its crystal structure can be the same as that of the Ti support in Example 1; the blade root is the TiAl alloy of Example 1, including γ phase and α2 phase.
[0067] Comparative Example 1 This comparative example provides a TiAl alloy whose preparation method differs from that of Example 3 in that: in S1, a Ti support with a relative volume fraction of 65% is designed, the support is a thick rod with a diameter of 1 mm; the forming parameters of the laser powder bed melting are: laser power of 190 W, scanning speed of 1100 mm / s, laser vector spacing of 90 μm, layer thickness of 25 μm, and laser energy density of 76 J / mm². 3 The rest is the same as in Example 1.
[0068] Comparative Example 2 This comparative example provides a TiAl alloy whose preparation method differs from that of Example 1 in that: in S3, a heat treatment step is performed at a temperature of 600°C for 72 hours; the rest is the same as in Example 1.
[0069] Comparative Example 3 This comparative example provides a TiAl alloy whose preparation method differs from that of Example 1 in that: in S1, the Ti scaffold is prepared by electron beam melting (EBM) process, and its forming parameters are: power of 1200W, scanning speed of 5800mm / s, scanning spacing of 0.13mm, and layer thickness of 50μm; the rest are the same as in Example 1.
[0070] Comparative Example 4 This comparative example provides a TiAl alloy whose preparation method differs from that of Example 1 in that: in S2, a pressure infiltration process is used to prepare a preform, the specific steps of which include: heating the aluminum melt to 800°C and holding it at that temperature for 20 minutes to ensure that Al is fully melted; after holding at that temperature, 0.8 MPa is introduced; under the pressure, the liquid metal infiltrates into the pores, and Ar is continuously introduced until the temperature drops to room temperature to form a dense composite material; the rest is the same as in Example 1.
[0071] Comparative Example 5 This comparative example provides a TiAl alloy whose preparation method differs from that of Example 2 in that step S3 is omitted, i.e., there is no heat treatment step in the preparation method; the rest is the same as that of Example 2.
[0072] Comparative Example 6 This comparative example provides a TiAl alloy whose preparation method differs from that of Example 1 in that: in S1, a Ti support with a relative volume fraction of 30% is designed, and the support is a thick rod with a diameter of 1 mm; the rest is the same as in Example 1.
[0073] Comparative Example 7 This comparative example provides a TiAl alloy, the preparation method of which refers to the prior art CN121017577 A.
[0074] Performance testing The mechanical property testing method of this invention refers to standard ISO 6892-1:2019. Yield strength refers to the stress at the point during the test where plastic deformation occurs without any increase in force, when a metallic material exhibits yielding. Maximum strength refers to tensile strength, i.e., the stress corresponding to the maximum force. Maximum strain refers to total elongation at fracture, i.e., the total elongation at fracture expressed as a percentage of the extensometer gauge length.
[0075] Mechanical properties were tested on Examples 1-4 and Comparative Examples 1-5, and the results are shown in Table 1.
[0076] Table 1. Mechanical property test results of Examples 1-5
[0077] As shown in Table 1, the TiAl alloy prepared by this invention has a yield strength ≥672MPa, a maximum strength ≥750MPa, and a maximum strain ≥9.0%. This indicates that the TiAl alloy prepared by the method of this invention has excellent strength and toughness.
[0078] Tests showed that the density of Example 1 was 99.5%, while that of Comparative Example 1 was 98.2%, indicating a significant decrease in density. This is because the high laser input energy density led to instability in the molten pool, resulting in numerous pores; simultaneously, insufficient local heat transfer caused incomplete fusion between powder particles, resulting in irregular pore morphology. Furthermore, Comparative Example 1 exhibited excessively low yield strength and insufficient toughness, failing to meet the requirements for turbine blade applications.
[0079] As can be seen from Comparative Example 2 and Example 1, the yield strength and maximum strain of Comparative Example 2 are both lower than those of Example 1. This is because the heat treatment temperature of Comparative Example 2 is insufficient, resulting in insufficient interdiffusion and penetration of Ti and Al elements, and thus failing to form a Ti3Al phase with a high volume ratio.
[0080] Comparative Example 3 uses electron beam melting to form a Ti scaffold. This method results in a high oxygen content and coarse metal grains due to the high-temperature powder bed, which significantly reduces the plasticity of the final TiAl alloy. Compared with electron beam melting, laser powder bed melting has significant advantages in preparing pure Ti scaffolds, avoiding the oxidation problems caused by the high-temperature powder bed and achieving higher forming accuracy.
[0081] Comparative Example 4, prepared using a pressure infiltration process, resulted in a TiAl alloy with more residual porosity, uneven distribution of the interfacial reaction layer, and poor overall microstructure continuity, leading to lower yield strength and maximum strain compared to Example 1. This indicates that during pressure-assisted sintering, the hot isostatic pressing process, due to the absence of inhomogeneity caused by liquid phase flow, exhibits superior overall microstructure uniformity and dimensional stability compared to pressure infiltration. Comparative Example 5, which did not undergo heat treatment of the preform, resulted in an alloy with lower yield strength and maximum strength than Example 2. This may be due to insufficient interdiffusion between Ti and Al elements caused by the lack of heat treatment.
[0082] Testing revealed that Comparative Example 6, using a Ti support with a relative volume fraction of 30%, exhibited a yield strength below 600 MPa, a maximum strength below 700 MPa, and a maximum strain <5%, indicating insufficient toughness in the prepared alloy. This is because the relatively low volume fraction of the Ti support resulted in mechanical properties that failed to meet the requirements for turbine blade applications.
[0083] Comparative Example 7 uses alloy powder to prepare TiAl alloy. During the preparation process, the alloy often exhibits cracking phenomena, and the strain of the prepared alloy is about 2%.
[0084] Figure 4 These are electron micrographs and EDS linear scans of Example 1. (From...) Figure 4 It can be seen that the Ti support voids are filled with Al metal, and the interfacial reaction layer between Ti metal and Al metal is uniformly distributed, forming Ti3Al, Al3Ti, and TiAl phases. This indicates that the preparation method of the present invention can achieve interdiffusion between Ti metal elements and Al metal elements, thereby forming alloys with different phases.
[0085] Figure 5 The images shown are the electron microscope image and EDS linear scan spectrum of Comparative Example 2. (From...) Figure 5 It can be seen that when the heat treatment temperature is 600℃, the mutual diffusion of Ti and Al elements is not as uniform as in Example 1, and Ti-rich or Al-rich phases are easily generated in the alloy.
[0086] Figure 4 and Figure 5Quantitative analysis of the changes in alloy composition at different heat treatment temperatures proved that the additive manufacturing composite process provided by this invention can achieve sufficient diffusion of elements, thereby forming a controllable Ti3Al phase or TiAl phase in different composition ranges, and the heat treatment process can further promote this microstructure evolution. Figure 6 This is a statistical diagram showing the phase composition of Example 1, Comparative Example 2, and Example 1 before heat treatment. Figure 6 It can be seen that the preform before heat treatment is mainly composed of the Ti phase. Compared with the preform before heat treatment, the phase composition of Comparative Example 2 shows little change in the volume fraction of each metal phase. The TiAl alloy of Example 1, by volume percentage, has the following phase composition: TiAl: 5.7%, Ti3Al: 61.8%, TiAl3: 0.6%, Ti: 26.8%, with the remainder being Al phase. The comparison shows that the heat treatment process promotes the interaction between Ti and Al, forming a large amount of α2 phase. In the preparation process of this invention, the pure Ti phase gradually evolves into the Ti3Al phase, and the pure Al phase gradually evolves into Al3Ti and then into the TiAl phase (see details...). Figure 7 This further illustrates that the additive manufacturing composite process provided by the present invention can achieve interdiffusion of elements, and through the flexible control of alloy composition and composite process, the phase composition of TiAl alloy can be controlled and the performance optimized in a targeted manner.
[0087] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art can make other variations or modifications based on the above description. It is neither necessary nor possible to exhaustively describe all embodiments here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a TiAl alloy, characterized in that, Includes the following steps: S1. Ti scaffolds were fabricated using a laser powder bed melting process; S2. Fill the Ti support with aluminum powder, seal it, and then perform hot isostatic pressing. S3. Perform heat treatment again to obtain the TiAl alloy; The energy density of the laser powder bed melting process is 60~70 J / mm². 3 The relative volume fraction of the Ti support is 40-70%; the heat treatment includes a first heat treatment at a temperature of 800-1400℃. The TiAl alloy forms a layered alloy phase at the interface between the titanium phase and the aluminum phase. The alloy phase includes Ti3Al phase and / or TiAl phase. The TiAl alloy is designed and prepared with different phase composition in different parts to meet the performance requirements of different parts by the difference in phase composition.
2. The preparation method according to claim 1, characterized in that, The parameters of the laser powder bed melting process are as follows: laser power of 120~200W, scanning speed of 600~1200mm / s, laser vector spacing of 80~120μm, and layer thickness of 20~40μm.
3. The preparation method according to claim 1, characterized in that, The hot isostatic pressing process includes: holding at 1200~1800℃ for 3~8h at a pressure of 1~3MPa; and then holding at 600~1000℃ for 4~6h at a pressure of 80~120MPa.
4. The preparation method according to claim 1, characterized in that, The heat treatment also includes a second heat treatment.
5. The TiAl alloy prepared by any of the preparation methods described in claims 1 to 4.
6. The TiAl alloy according to claim 5, characterized in that, The phase composition of the TiAl alloy, by volume percentage, is TiAl: 2~8%, Ti3Al: 50~70%, TiAl3: 0.1~1%, with the remainder being Ti phase and / or Al phase.
7. The application of the TiAl alloy of claim 5 in the preparation of turbine blades.
8. A TiAl alloy turbine blade, comprising a blade outer shell, a blade inner layer, and a blade root; characterized in that, The blade root is the TiAl alloy as described in claim 5, and the alloy composition of the blade root is: Al: 35~47 at.%, Ti: 53~70 at.%, and the alloy composition of the outer shell of the blade body is Al: 48~56 at.%, Ti: 44~52 at.%.
9. The TiAl alloy turbine blade according to claim 8, characterized in that, In the TiAl alloy turbine blade, the outer shell of the blade is a single γ-phase TiAl alloy, and the inner layer of the blade is composed of Ti support, with a relative volume fraction of 40-60% for the Ti support in the inner layer of the blade.
Citation Information
Patent Citations
High-performance gamma-based titanium-aluminum alloy and additive manufacturing method thereof
CN121017577A
A method to improve the comprehensive performance of alloy materials based on the principle of "weaving injection molding"
CN120394898B
